Factors influence customers selection criteria towards Islamic Banking / Raja Nurul Akhma Raja Abdullah - Raja Abdullah, Raja Nurul Akhma (Faculty of Business Management, 2017)
The emergence of Islamic banking system has becoming new platform to do banking transaction by modern customers nowadays. Islamic Banking received a wide acceptance among customers around the globe (Iqbal and Molyneux, 2005). Islamic banking continues to expand from time to time and becoming a market that could compete with the conventional banking institutions across the world (Ariss et al., 2010). However, The increase of competition in banking over the past decades has placed a lot of strain on bank earning and the pressure also increase with many other banking and financial institutions has entering new market along with the variety products and services offered in order to ensure position and increase their earnings in the market (Ariss et al., 2010). The fierce competition between Islamic and conventional banking sector makes it vital for the Islamic banks to ascertain the factors that could lead the customers to choose Islamic banks. Thus, the purpose of this study is to identify the factors that influence customer's selection towards Islamic Banking. Therefore, this study would like to concentrate more on inner factors that influence customers to select Islamic banking such as religiosity, ATM service, cost and benefit, banks' attractiveness and financial security that influence customers to select Islamic banking. The questionnaire will be distribute to 150 customers of Bank Islam Malaysia Berhad and Bank Muamalat Malaysia Berhad in Segamat by using convenience sampling. Statistical Package for Social Science (SPSS) used to analyze the data and method for data analyze using Multiple Linear Regression. The results and findings shows that religiosity becomes the most preferable factor that customers considered in selecting Islamic banking. This is due to the need of Shariah compliancy in the financial transaction nowadays.